PHILOSOPHICAL ANALYSIS OF THE SCIENTIFIC HERITAGE OF IS‟HOQXON TO„RA IBRAT (Scientific journal of the Fergana State University, 2026)
This article analyzes the life of our great ancestor, the leader of the Jadid movement of the Fergana Valley,Ishakhon Tura Dzhunaydullakhoja ugli Ibrat, his rich legacy in the socio-political, educational, literary, artistic and scientific spheres, and also examines the issues of introducing the progressive ideas he put forward into the consciousness of young people. At the same time, unexplored aspects ofIbrat‘s pedagogical activity are covered in detail.